Modeling liquid-liquid interface level in a horizontal three-phase separator with a bucket and weir. Issue 11 (2nd November 2018) - Deng, Chaojun; Huang, Weixing; Wang, Haoyuan; Lan, Hongqiang; Xu, Boya
ABSTRACT: The flow behavior in a three-phase separator with a bucket and weir was analyzed, and a theoretical equation for calculating the liquid-liquid interface level ( H H ) in gravity separation zone was derived. The analysis indicates that the H H increases as the flow rate and the density ratio of heavy to light liquid increase, and decreases linearly with increasing height difference between heavy and light liquid overflow weirs. The calculated H H under different operating conditions is in good agreement with the experimental. With the proposed equation, the thicknesses of heavy and light liquid layers can be calculated, and then the minimum lengths of two phase layers required for separation can be determined separately. From the minimum lengths it can be clearly indicated that the governing step of liquid-liquid separation is in heavy or light liquid layers, hence the sizing of the separator can be optimized. GRAPHICAL ABSTRACT: